Organoid models of the pituitary gland in health and disease - Laporte, Emma; Vankelecom, Hugo (Frontiers in Endocrinology, 2023)
The pituitary gland represents the hub of our endocrine system. Its cells produce specific hormones that direct multiple vital physiological processes such as body growth, fertility and stress. The gland also contains a population of stem cells which are still enigmatic in phenotype and function.Appropriate research models are needed to advance our knowledge on pituitary (stem cell) biology.Over the last decade, 3D organoid models have been established, either derived from the pituitary stem cells or from pluripotent stem cells, covering both healthy and diseased conditions. Here, we summarize the state-of-the-art of pituitary-allied organoid models and discuss applications of these powerful in vitro research and translational tools to study pituitary development, biology and disease.